Revision of the ant genus Iridomyrmex (Hymenoptera: Formicidae) - Heterick, Brian E.; Shattuck, Steve (Zootaxa, 2011)
The world fauna of the dolichoderine ant genus Iridomyrmex (Hymenoptera: Formicidae) is revised. Seventy-nine species are recognised, 31 described as new. Four species are removed from Iridomyrmex: I. butteli (Forel) to Chronoxenus, I. extensus Emery to Anonychomyrma and I. krakatauae Wheeler and I. latifrons Karavaiev to Tapinoma. Twenty-five species and subspecies pass into synonymy: I. emeryi Crawley is synonymised under I. victorianus Forel (itself raised to species), I. vicinus Clark is synonymised under I. splendens Forel (itself raised to species), I. wingi Donisthorpe is synonymised under I. pallidus Forel (itself raised to species), I. gracilis Lowne (a preoccupied name) is synonymised under I. bicknelli Emery, I. mimulus Shattuck is synonymised under I. viridigaster Clark, I. albitarsus Wheeler and I. notialis Shattuck are synonymised under I. calvus Emery, I. obscurus Crawley is synonymised under I. suchieri Forel (itself raised to species), I. greensladei Shattuck is synonymised under I. purpureus, I. variscapus Shattuck is synonymised under I. bigi Shattuck, and I. meinerti Forel is synonymised under I. anceps Roger. Of the subspecies, I. anceps formosae Forel, I. anceps ignobilis Mann, I. rufoniger metallescens Emery, I. anceps sikkimensis Forel and I. anceps watsonii Forel are synonymised under I. anceps, Iridomyrmex bicknelli splendidus Forel is synonymised under I. bicknelli Emery, I. rufoniger fusciventris Forel is synonymised under I. brunneus Forel (itself raised to species), I. chasei concolor Forel and I. chasei yalgooensis Forel are synonymised under I. chasei Forel, I. rufoniger incertus Forel is synonymised under I. pallidus, I. rufoniger domesticus Forel and I. rufoniger septentrionalis Forel are synonymised under I. rufoniger Lowne, and I. mattiroloi parcens Forel is synonymised under I. victorianus. In addition to the five taxa mentioned above, the subspecies I. bicknelli azureus Viehmeyer, I. bicknelli brunneus Forel, I. mattiroloi continentis Forel, I. gracilis minor Forel, I. gracilis rubriceps Forel and I. gracilis spurcus Forel are raised to species. A single species, I. bicknelli luteus Forel, could not be identified and is treated as species inquirenda. A key to workers of the genus is supplied. Lectotypes are designated for I. brunneus Forel, I. chasei Forel, I. conifer Forel, I. discors Forel, I. minor Forel, I. mjobergi Forel, I. pallidus Forel, I. suchieri Forel and I. victorianus Forel. Neotypes are established for I. anceps (Roger), I. parcens Forel and I. rufoniger (Lowne). Five fossil species are considered to belong to Iridomyrmex, although only one of these is supported by rigorous morphological data. Four fossil species are regarded as incertae sedis within the genus. The following fossil-based species are removed from Iridomyrmex (all new combinations): geinitzi Mayr to Anonychomyrma, haueri Mayr to Dolichoderus, oblongiceps Wheeler to Eldermyrmex (gen. n.) and bogdassarovi Nazaraw, Bagdasaraw & Uriew to Liometopum.